Implementasi Alat Pendeteksi Dini Kebakaran di Kelurahan Bukit Duri Berbasis Internet of Things (IoT) - Tri Wahyudi; Sultan Faqih Fiddin; Donny Alif Utama; Syarif Hidayatullah; Rival Ismail (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2023)
There are many densely populated areas in Indonesian territory, especially in DKI Jakarta wards. In DKI Jakarta there are many sub-districts with a large population. It is recorded that there are 52,230 people living in 2.29 km2 of the village's land area. Therefore in a densely populated area and there are many buildings the rate of fire is high. Fire incidents cannot be predicted by anyone, so early fire detection devices are needed. the author wants to create a fire detection system using the Arduino Atmega328p microcontroller based on the internet of things (IoT) using a fire sensor, and an MQ-2 gas sensor to get 9 early symptoms of a fire and can be heard via an alarm in real-time. As well as being able to provide information to the owner of this tool and be able to find out if early signs of fire appear. So as to reduce the risk or minimize losses caused by fire accidents and can reduce the occurrence of fire accidents..